Urbanization under a Changing Climate Impacts on Urban Hydrology - Valeo, Caterina; Kasiviswanathan, K.S; He, Jianxun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In response to the increasing urbanization, advances in the science of urban hydrology have improved urban water system management, creating more livable cities in which public safety and health, as well as the environment, are protected. The ultimate goal of urban water management is to mimic the hydrological cycle prior to urbanization. On top of urbanization, climate change, which has been demonstrated to alter the hydrological cycle in all respects, has introduced additional challenges to managing urban water systems. To mitigate and adapt to urbanization under a changing climate, understanding key hydrologic components should expand to include complex issues brought forth by climate change. Thus, effective and efficient measures can be formulated. This Special Issue of Water presents a variety of research papers that span a range of spatial and temporal scales of relevance in different societies' efforts in adapting to the eminent changes in climate and the continuous changes in the landscape. From mitigating water quality in permeable pavements and bioretention swales to understanding changes in groundwater recharge in large regions, this Special Issue examines the state-of-the-art in sustainable urban design for adaptation and resiliency.